Asiatic acid ameliorates CC l4-induced liver fibrosis in rats: involvement of Nrf2/ARE, NF-κB/IκBα, and JAK1/STAT3 signaling pathways - Fan J; Chen Q; Wei L; Zhou X; Wang R; Zhang H (Dove Medical Press, 2018)
Jie Fan,1,* Qingshan Chen,2,* Liwen Wei,1 Xiaoming Zhou,3 Rong Wang,4 Hai Zhang1 1Department of Pharmacy, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, Shanghai 201204, China; 2Department of Pharmacy, Shanghai Eastern Hepatobiliary Surgery Hospital, Second Military Medical University, Shanghai 200438, China; 3Department of Endocrinology and Metabolism, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, China; 4Department of Pharmacy, Shanghai 9th People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 201999, China *These authors contributed equally to this work Purpose: Currently, there are no effective therapies for liver fibrosis; hence, the development of anti-liver fibrosis agents is urgently needed. Here, we attempted to investigate the therapeutic effect and mechanism of asiatic acid (AA) on liver fibrosis, mainly focusing on the impact of AA on nuclear erythroid 2-related factor 2/antioxidant response element (Nrf2/ARE), nuclear factor-kappa B (NF-κB)/IκBα, and JAK1/signal transducer and activator of transcription 3 (STAT3) signaling pathways. Methods: Rats were induced liver fibrosis by carbon tetrachloride (CCl4) for 6 weeks and concomitantly treated with AA (5 and 15 mg/kg) or vehicle by daily gavage. After AA treatment, the morphology of liver tissue was analyzed by H&E and Masson’s trichrome staining, and serum biochemical indicators were also assayed. Thereafter, the protein levels of Nrf2, HO-1, NQO-1, GCLC, NF-κB, IκBα, JAK1, p-JAK1, STAT3, and p-STAT3 were determined by Western blotting. Results: Our results showed that AA treatment dramatically ameliorated CCl4-induced oxidative stress, inflammation, and fibrosis in rats. The expression of nuclear Nrf2 was increased after AA treatment, whereas cytoplasm Nrf2 levels were decreased. The protein expression of Nrf2 target proteins including HO-1, NQO-1, and GCLC was significantly increased by AA treatment. Furthermore, AA treatment decreased the levels of nuclear NF-κB to inhibit NF-κB/IκBα signaling pathway. In addition, we also found that AA treatment regulated JAK1/STAT3 signaling by decreasing the phosphorylation levels of JAK1 and STAT3. Conclusion: These results demonstrate that AA ameliorates CCl4-induced liver fibrosis in rats by regulating Nrf2/ARE, NF-κB/IκBα, and JAK1/STAT3 signaling pathways, which suggests that AA might be a new antifibrosis agent that improves liver fibrosis. Keywords: asiatic acid, liver fibrosis, Nrf2-ARE, NF-κB/IκBα, JAK1/STAT3